Pentingnya Evaluasi dalam Proses Pembelajaran dan Konsekuensi Manipulasi - Magdalena, Ina; Damaiyanti, Febrika; Khotimah, Khusnul; Lestari, Rizkia Dwi (Lembaga Yasin AlSys, 2023)
Evaluation includes measuring and assessing. The process of evaluating the process of student growth in the teaching and learning process. Each student has abilities that vary from fast, medium and slow. Before doing things that need to be considered are evaluation, evaluation, and evaluation. However, now teachers pay less attention to this matter and many teachers manipulate student grades. The consequences of manipulating grades will be bad for students.The research method used in gathering information was by using the observation method and conducting interviews with the school principal at SD Muhammadiyah 35.. The results showed that the obstacles encountered during the assessment were the assessment of attitudes, skills, and also how to describe grades on report cards. Efforts to overcome these obstacles are hoping that the scope of the assessment is expected to be minimized. And teachers hope that the Government will provide deeper training to teachers who do not understand the 2013 Curriculum.